Study of vaginal cytology in reproductive age group women attending tertiary care teaching hospital - Singh, Neelam; Purohit, Ashish; Tiwari, Varsha; Shyam, Saroj (International Journal of Medical Research and Review, 2015)
Introduction-Lesions of the cervix are the commonest causes of chronic ill health in gynecologicalpractices. The cervix is a specially modified part of uterus with a histological and physiological entity of its own. It probably constitutes the most neglected and damaged part of female body.The accurate study of these vaginal and cervical lesions are needed because of chronic disability of the patient in the form of low backache, vaginal discharge, primary or secondary sterility and later predisposition to malignancy. Materials and Methods- A total of 200 smears were studied from 200 women of reproductive age group attending gynecologicaloutpatient department and antenatal clinic of sultaniaZanana hospital, Bhopal who complained of symptoms like backache, discharge, and irregular vaginal bleeding. A detailed clinical and vaginal examination was done in every case and smears were collected for exfoliative cytology.Analysis of results were done by Odds ratio and multivariate logistic regression. Results- 200 clinically diagnosed cases of benign lesions of cervix were taken up for detailed clinical and cytological study. Erosion was the commonest among all benign lesions, which was 58.5% . Next common lesion was chronic cervicitis 20%, chronic cervicitis with erosion 9%, 7% endocervicitis, 2% cervical polyp, 0.5% carcinoma cervix,and 3 % showed metaplasia on cytological examination. Conclusion-Nonmalignant cervical lesions are extremely common, of these , cervical erosion and non- specific cervicitis are most frequently encountered.These are frequent cause of morbidity in women of reproductive age group, which if neglected progresses to malignancy with significant morbidity and mortality. Close follow up and histiologic examinations are necessary to avoid unnecessary spread of neoplastic disease and untimely death of patients. awareness about diseases in women of reproductive age group and diagnostic utility ofpapanicolau smear test is also a must.